Recent advances in organocatalytic asymmetric oxa-Michael addition triggered cascade reactions - Wang, Yu; Da-Ming, Du (Organic chemistry frontiers an international journal of organic chemistry, 2020)
The oxa-Michael cascade reaction, as an important part of the Michael reaction, has also been significantly developed over the recent decade. This is because the problem of the reactivity and selectivity of the addition reactions of oxygen nucleophiles to conjugated systems has been solved by different organocatalysts and reaction conditions. Therefore, using various efficient strategies, many novel and potentially bioactive chiral compounds with excellent yields and stereoselectivities have been synthesized. In this review, we summarize the recent advances in organocatalytic asymmetric oxa-Michael addition triggered cascade reactions for the stereoselective synthesis of heterocyclic compounds.